Fish reproductive cells collection of the Institute for Problems of Cryobiology and Cryomedicine of the NAS of Ukraine: history, significance and perspectives - Khomenko, Andrii; Fomenko, Kostiantyn; Cherepanov, Valeriy (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):245